Feasibility study quality drinking water refillable in sub districts Tampan Pekanbaru City - Afni Meldawati; Nofrizal Nofrizal; Viktor Amrifo (Program Pascasarjana Universitas Riau, 2017)
Water is one of the most important components in human life. Water used by Refill drinking water depots mostly comes from groundwater, contaminated ground water will result in refill drinking water depots water quality not being eligible. The large demand of people in Kecamatan Tampan using refill drinking water has caused the proliferation of Refill drinking water depots located in sub district Tampan Pekanbaru city. This research was conducted of December 2016 - February 2017. The research was conducted in December 2016 - February 2017, the materials used were raw water (ground water) and drinking water refill the production of Drinking Water Refill Depot. Tools namely 12 sterile bottles and stationery, and sheet checklist. The research method used is survey method, population of 160 Depot of Drinking Water Refill, total sample 114 Depot of Drinking Water Refill. Result of research indicate that sanitation hygiene condition is 60,5% not fulfill requirement, material feasibility 58,8% not fulfill requirement and quality of refill drinking water come from ground water as much 56,1% not fulfill requirement. There is a relationship between hygiene sanitation refill drinking water depots with the quality of drinking water refill originated from groundwater in the work area sub district Tampan Pekanbaru city with p value = 0,026. There is a relationship between the feasibility of raw materials of drinking water refill from ground water with refill drinking water quality comes from ground water in the work area sub district Tampan Pekanbaru with p value = 0.008. The most influential variable on the quality of drinking water refill in sub district Tampan is hygiene refill drinking water depots hygiene with p value 0,01 and a 96% chance of refill drinking quality not eligible. As a conclusion the quality of drinking water refill in Kecamatan Tampan Pekanbaru City influenced by sanitation hygiene.